PERENCANAAN ULANG PERKERASAN TAXIWAY N1-NP2 DARI FLEXIBLE KE RIGID DI BANDAR UDARA JUANDA SURABAYA - Fahri Gunawan; Darmadi (JURNAL TEKNIK SIPIL-ARSITEKTUR, 2023)
Juanda Airport Surabaya have increase in annual flight, which it result in decreasing the capable of airside to facilitate the growth of aircraft movement. The damage of NP2’s taxiway caused by pavement temperature that reaches softening point of taxiway pavement and the height of water table in that area so when damage occur it may disturb the aircraft’s take off, so that need assessment to improving facility, which’s the plan is improving facility of NP2’s taxiway. In the plan to develop a taxiway facility, it able to plan the improving the taxiway using FAA (Federal Aviation Administration) in geometric calculation and pavement thickness with manual method and compare to software support program FAARFIELD, then the result entered in COMFAA. The plan to improving pavement are changing existing pavement from flexible pavement to rigid pavement. After comparison, the result of calculation for each pavement layer are geometric of taxiway with 806,77m x 30m, with each thickness of foundation is 10 inch and the thickness of concrete slab is 15,2 inch. Then obtain the value of PCN with 88,2 and the change of flexible pavement to rigid pavement.